Human Rights Enforcement in Indonesia towards the Implementation of Pancasila Values - Yustitianingtyas, Levina; Irawan, Anang Dony; Dedy Stansyah (JUSTISI, 2025)
The study aims to determine the extent of the Indonesian Government's efforts to provide protection of Human Rights (HAM) in order to remain firmly adhered to the values of Pancasila. This research method is normative juridical, with a statutory approach using data analysis techniques and processing the results of primary material collection and secondary material collection. Novelty of this research provides a more comprehensive view of efforts to restore and improve human rights enforcement in post-New Order Indonesia, especially in the face of human rights violations that remain unresolved, such as the Tanjung Priok, Aceh, Semanggi, East Timor and Papua cases. This study also offers a solution based on Pancasila values as the basis for making legal policies, which have not been thoroughly applied by the government in law enforcement practices in Indonesia. The study results show that human rights enforcement in Indonesia is still far from the true meaning of justice, because it is still influenced by the interests of the authorities, law enforcement officials, and so on. Included in the enforcement of human rights is also still very far away from the values of Pancasila. Conclusion of this paper is that all formulations and policies of the State must be guided by the values of Pancasila, especially in the enforcement of human rights in Indonesia, although many cases that occur in law enforcement do not reflect Pancasila as the identity of the nation.